Графон як засіб експресивізації художнього тексту - Хайчевська, Тетяна Миколаївна; Khaichevska, Tetiana M. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті увагу зосереджено на вивченні графону як одного із засобів посилення експресивності художнього тексту. Зроблено спробу простежити взаємодію модифікованої форми написаного з появою додаткової смислової інформації при його інтерпретації, що сприяє досягненню автором поставленої мети. Описано орфографічні та/або графічні зміни написання, які ілюструють явище графону у сучасній французькій художній прозі. Graphon as the Means of Fiction Text Expressivization. In recent decades the interest of linguists to various innovations in the field of graphics and spelling of printed texts belonging to different genres has been increasing. The deliberate distortion of the graphic form or spelling of a word entails the changes in its perception. The original and/or non-normative use of graphic units creates new shades of meaning. The article focuses on the study of a graphon as the means of the fiction text expressivity intensification, as this figure of speech covers the majority of stylistically relevant deviations from the rules of spelling and/or graphic standard. In this article an attempt is made to find out the relationship between the modification of words or phrases at the level of graphics and/or spelling and the appearance of additional meaningful information in their interpretation.
Graphon as the Means of Fiction Text Expressivization
Keywords: графон; експресивність тексту; орфографічна норма; графічна форма; графічний новотвір; експресивізація